MODERN INFORMATION SYSTEMS IN MEDICINE (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article discusses the role of modern information systems in the medical field, their effectiveness in the healthcare system, and their importance in improving the quality of medical services. The possibilities of electronic medical records, clinical decision support systems, telemedicine, and information systems based on artificial intelligence are analyzed. Research results show that the use of modern information technologies optimizes medical processes, increases diagnostic accuracy, and improves the efficiency of working with patients.
Keywords: Medicine, information systems, electronic medical record, telemedicine, artificial intelligence, digital healthcare.